2009
DOI: 10.1007/s11011-009-9165-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise on synaptophysin and calcium/calmodulin-dependent protein kinase levels in prefrontal cortex and hippocampus of a rat model of developmental stress

Abstract: Stress affects the brain differently depending on the timing, duration and intensity of the stressor. Separation from the dam for 3 hours per day is a potent stressor for rat pups which causes activation of the hypothalamic-pituitary-adrenal (HPA) axis, evidenced by increased plasma levels of adrenocorticotropin (ACTH) and glucocorticoids. Behaviourally, animals display anxiety-like behaviour while structurally, changes occur in neuronal dendrites and spines in the hippocampus and prefrontal regions involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…Furthermore, 4 weeks of aerobic exercise did not induce significant changes in synaptophysin expression compared with that in all other groups. Our finding is in agreement with previous studies that demonstrated that hippocampal levels of this protein were not altered after 3, 7, 15 (Ferreira et al, 2011) and 20 (Hescham et al, 2009) days of forced and voluntary exercise. Conversely, other reports have demonstrated increased expression of synaptophysin in the hippocampus (Cassilhas et al, 2012a;Vaynman et al, 2004), striatum and substantia nigra (Ferreira et al, 2010) after different exercise regimens.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, 4 weeks of aerobic exercise did not induce significant changes in synaptophysin expression compared with that in all other groups. Our finding is in agreement with previous studies that demonstrated that hippocampal levels of this protein were not altered after 3, 7, 15 (Ferreira et al, 2011) and 20 (Hescham et al, 2009) days of forced and voluntary exercise. Conversely, other reports have demonstrated increased expression of synaptophysin in the hippocampus (Cassilhas et al, 2012a;Vaynman et al, 2004), striatum and substantia nigra (Ferreira et al, 2010) after different exercise regimens.…”
Section: Discussionsupporting
confidence: 94%
“…However, expression level of CaMKIIα in the hippocampus has been found to be dependent on NMDA receptor activity (Thiagarajan et al. 2002), intracellular calcium availability (Alier and Morris 2004) and voluntary exercise (Hescham et al. 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of expression of the different PKA subunits are subject to regulation by hormones acting through Gprotein coupled receptors, by mitogen signals through receptors associated with protein tyrosine kinases, by steroid hormones, as well as by cAMP-mediated regulation of PKA subunits acting through gene transcription and mRNA stability (for review see Skalhegg and Taskén 2000). However, expression level of CaMKIIa in the hippocampus has been found to be dependent on NMDA receptor activity (Thiagarajan et al 2002), intracellular calcium availability (Alier and Morris 2004) and voluntary exercise (Hescham et al 2009). The facts that subunits of both PKA and CaMKII are developmentally regulated (Bayer et al 1999;Skalhegg and Taskén 2000) and that early undernutrition could epigenetically affect (silencing or switching-on) the expression of a number of genes involved in development of the brain and other organs, have led to the hypothesis that the majority of the enduring or permanent morpho-functional deficits programmed by undernutrition during fetal life are the results of such an epigenetic influence on gene expression (Gómez-Pinilla 2008; Langley-Evans 2009).…”
Section: Discussionmentioning
confidence: 99%
“… 86 Treadmill exercise has also been shown to enhance synaptophysin and CamKII protein expression in the ventral hippocampus of both separated and non-separated Sprague Dawley rats on PND 65. 87 No differences in protein expression were noted in the dorsal hippocampus or prefrontal cortex in exercised versus non-exercised (both stressed and non-stressed), 87 indicating that the effect of exercise may in fact be brain-region-specific.…”
Section: Exercise Modulates Early Stress-induced Changesmentioning
confidence: 99%